Perceived Racial Discrimination and Marijuana Use a Decade Later; Gender Differences Among Black Youth - Assari, Shervin; Mistry, Ritesh; Lee, Daniel B.; Caldwell, Cleopatra Howard; Zimmerman, Marc A. (Frontiers in Pediatrics, 2019)
Background: Despite evidence documenting gender differences in the association between perceived racial discrimination (PRD) and substance use, we are not aware of longitudinally studies with long term follow up data on gender differences in the link between baseline PRD and subsequent marijuana use (MU). Objective: The current longitudinal study tested gender differences in the association between PRD and average subsequent MU among young Black youth. Methods: Current study included a cohort 595 Black (278 males [46.7%] and 317 females [53.3%]) 9th grade students who were followed for up to 18 years from 1994 (mean age 15) to 2012 (mean age 32). All participants were selected from an economically disadvantaged urban area in the Midwest, United States. The independent variable, PRD measured in 1999. Outcome was average MU based on eight-time measurement of MU between 1999 and 2012. Covariates included socio-demographics (age, family structure, and parental employment) at 1994. Gender was the focal moderator. Linear regression model was used to analyze data. Results: In the pooled sample, PRD in 1994 was not associated with average MU from 1999 to 2012. We did, however, find a significant interaction between PRD and gender on average MU, suggesting stronger association for males than females. In gender-specific models, PRD predicted MU for males but not for females. Conclusion: The association between PRD and marijuana use may depend on gender, with males being susceptible to the effect of PRD, while females were not. This finding is in support of the literature showing that Black males are more strongly affected by PRD.